Oxidative Stress Promotes Corticosteroid Insensitivity in Asthma and COPD - Brandon W. Lewis; Maria L. Ford; Lynette K. Rogers; Rodney D. Britt (MDPI AG, 2021)
Corticosteroid insensitivity is a key characteristic of patients with severe asthma and COPD. These individuals experience greater pulmonary oxidative stress and inflammation, which contribute to diminished lung function and frequent exacerbations despite the often and prolonged use of systemic, high dose corticosteroids. Reactive oxygen and nitrogen species (RONS) promote corticosteroid insensitivity by disrupting glucocorticoid receptor (GR) signaling, leading to the sustained activation of pro-inflammatory pathways in immune and airway structural cells. Studies in asthma and COPD models suggest that corticosteroids need a balanced redox environment to be effective and to reduce airway inflammation. In this review, we discuss how oxidative stress contributes to corticosteroid insensitivity and the importance of optimizing endogenous antioxidant responses to enhance corticosteroid sensitivity. Future studies should aim to identify how antioxidant-based therapies can complement corticosteroids to reduce the need for prolonged high dose regimens in patients with severe asthma and COPD.